Evaluation of phages and liposomes as combination therapy to counteract Pseudomonas aeruginosa infection in wild-type and CFTR-null models - Cafora, Marco; Poerio, Noemi; Forti, Francesca; Loberto, Nicoletta; Pin, Davide; Bassi, Rosaria; Aureli, Massimo; Briani, Federica; Pistocchi, Anna; Fraziano, Maurizio (Frontiers in Microbiology, 2022)
Multi drug resistant (MDR) bacteria are insensitive to the most common antibiotics currently in use. The spread of antibiotic-resistant bacteria, if not contained, will represent the main cause of death for humanity in 2050. The situation is even more worrying when considering patients with chronic bacterial infections, such as those with Cystic Fibrosis (CF). The development of alternative approaches is essential and novel therapies that combine exogenous and host-mediated antimicrobial action are promising. In this work, we demonstrate that asymmetric phosphatidylserine/phosphatidic acid (PS/PA) liposomes administrated both in prophylactic and therapeutic treatments, induced a reduction in the bacterial burden both in wild-type and cftr-loss-of-function (cftr-LOF) zebrafish embryos infected with Pseudomonas aeruginosa (Pa) PAO1 strain (PAO1). These effects are elicited through the enhancement of phagocytic activity of macrophages. Moreover, the combined use of liposomes and a phage-cocktail (CK), already validated as a PAO1 “eater”, improves the antimicrobial effects of single treatments, and it is effective also against CK-resistant bacteria. We also address the translational potential of the research, by evaluating the safety of CK and PS/PA liposomes administrations in in vitro model of human bronchial epithelial cells, carrying the homozygous F508del-CFTR mutation, and in THP-1 cells differentiated into a macrophage-like phenotype with pharmacologically inhibited CFTR. Our results open the way to the development of novel pharmacological formulations composed of both phages and liposomes to counteract more efficiently the infections caused by Pa or other bacteria, especially in patients with chronic infections such those with CF.